Mangrove community-based management in Eastern Africa: experiences from rural Mozambique - Macamo, Célia da Conceição Felisberto; Inácio da Costa, Fátima; Bandeira, Salomao; Adams, Janine Barbara; Balidy, Henriques Jacinto (Frontiers in Marine Science, 2024)
This study investigated a community-based management system in a mangrove dependent community in central Mozambique and its adequacy as a management tool for conservation. After unsustainable exploitation that led to mangrove deforestation, the local community engaged in a restoration and management program that started in the late 1990s. Local norms were delineated by the Natural Resources Management Committee (NRMC) aiming at (1) reducing extractive uses by introducing alternative income generating activities and alternative sources of fuel wood; (2) awareness and mangrove planting and (3) law enforcement. Ten hectares of forest have been rehabilitated since the program started. However, the management system does not have means to exclude illegal cutters nor to enforce mangrove use regulatory and sanctioning mechanisms, due to financial and resource shortages affecting the NRMC and formal enforcing authorities. More involvement from government authorities and other stakeholders is needed to provide assistance with law enforcement as well as to explore opportunities for carbon trading, tourism and payment for ecosystem services. Other recommendations for improvement of the system include the development of a community management plan and creating alternatives to mangrove products and income. Mangrove communitybased management is increasingly advocated in many developing countries to promote sustainable utilization of resources and conservation. Understanding the reasons behind the limited success and lessons learnt at this site will guide similar programs elsewhere in Mozambique and other parts of the globe.